HUMAN RESOURCE MANAGEMENT IN FORMING THE SPIRIT OF LIFE LONG LEARNERS AT SDIT MUTIARA INSAN SUKOHARJO - Indriyani, Indriyani; Utami, Datien Eriska; Waluyo, Waluyo (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to find out human resource management in the formation of a lifelong learning spirit at SDIT Mutiara Insan Sukoharjo. The method used in this study is a descriptive qualitative method of research typefield research. The results of the research on human resource management in the formation of a lifelong learning spirit at SDIT Mutiara Insan Sukoharjo which has been conducted are as follows: a) recruitment and selection, recruitment and selection teacher SDIT Mutiara Insan Sukoharjo is strict in ensuring that teachers have competencies and visions that are in line with the school. b) Professional Development, Professional self-development of teachers towards rapid technological developments and the ever-changing needs of students needs to be done so that teachers can adapt quickly. c) Performance Evaluation, carried out as a control for teachers who may still use old methods that may no longer be suitable for the needs and diversity of today's students in order to build a culture of critical and contextual thinking. d) Motivation and Empowerment, starting to become a teacher Life Long Learnerwhich is fun, can be done such as: creating learning goals, learning from small things, changing the way of learning to be fun, building an ecosystem of learning teachers, leadership support.